The Golgi as a “Proton Sink” in Cancer - Galenkamp, Koen M. O.; Commisso, Cosimo (Frontiers in Cell and Developmental Biology, 2021)
Cancer cells exhibit increased glycolytic flux and ATP hydrolysis. These processes increase the acidic burden on the cells through the production of lactate and protons. Nonetheless, cancer cells can maintain an alkaline intracellular pH (pHi) relative to untransformed cells, which sets the stage for optimal functioning of glycolytic enzymes, evasion of cell death, and increased proliferation and motility. Upregulation of plasma membrane transporters allows for H+ and lactate efflux; however, recent evidence suggests that the acidification of organelles can contribute to maintaining an alkaline pHi in cancer cells and thereby support tumor growth. The Golgi is such an acidic organelle, with resting pH ranging from 6.0-6.7. Here, we delineate the proton channels involved in Golgi acidification and the ion channels that influence this process. Furthermore, we discuss ion channel regulators that can affect Golgi pH and Golgi-dependent processes that may contribute to pHi homeostasis.